2016
DOI: 10.1001/jama.2015.18318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D3Supplementation During Pregnancy on Risk of Persistent Wheeze in the Offspring

Abstract: IMPORTANCE Observational studies have suggested that increased dietary vitamin D intake during pregnancy may protect against wheezing in the offspring, but the preventive effect of vitamin D supplementation to pregnant women is unknown. OBJECTIVE To determine whether supplementation of vitamin D 3 during the third trimester of pregnancy reduces the risk of persistent wheeze in the offspring. DESIGN, SETTING, AND PARTICIPANTS A double-blind, single-center, randomized clinical trial conducted within the Copenhag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
329
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 295 publications
(345 citation statements)
references
References 38 publications
9
329
2
5
Order By: Relevance
“…A total of 31 of them developed bronchopulmonary dysplasia (BPD) [Onwuneme et al 2015]. A recent RCT from Denmark studied 623 pregnant women [Chawes et al 2016]. Focusing mainly on offspring respiratory health, the group reported that daily supplementation with 2400 IU vitamin D 3 from week 24 until week 1 postpartum had a positive impact.…”
Section: Maternal Hypovitaminosis D Impact On Neonatal Infections Andmentioning
confidence: 99%
“…A total of 31 of them developed bronchopulmonary dysplasia (BPD) [Onwuneme et al 2015]. A recent RCT from Denmark studied 623 pregnant women [Chawes et al 2016]. Focusing mainly on offspring respiratory health, the group reported that daily supplementation with 2400 IU vitamin D 3 from week 24 until week 1 postpartum had a positive impact.…”
Section: Maternal Hypovitaminosis D Impact On Neonatal Infections Andmentioning
confidence: 99%
“…[9][10][11] Also, epidemiologic studies have suggested that maternal vitamin D intake 12, 13 as well 82 as vitamin D levels in blood [14][15][16] were inversely associated with respiratory tract infections and 83 other wheezing illnesses, presumably because of its multiple immune effects including induction 84 of antibacterial responses and modulation of T-lymphocytes to suppress inflammation. 17,18 Data 85 from randomized clinical trials are sparse, but two recently-published trials reported a non-86 significant more than 20% reduced risk of persistent wheeze/asthma at age 0-3 years from 87 prenatal vitamin D supplementation 19,20 In addition to the relatively short follow-up period, the 88 investigators acknowledged that the studies might be underpowered. Another systematic review of 23 published articles including 9 cross-sectional, 2 case-control, 93 and 12 cohort studies in both children and adults suggested that higher serum levels of 25- effect on development of asthma in childhood.…”
mentioning
confidence: 99%
“…After maternal vitamin D supplementation, rate of wheezing development was found to be low at 3-5 years of age (but no relation with asthma incident at 5 years of age) [28,29]. Between maternal vitamin D 2.800 IU/ day and 400 IU/day supplementation, there was no significant difference for allergy development at 3 years of age [30]. Another study performed in UK study demonstrated that high maternal plasma [25(OH) D3] level during late pregnancy was found to be associated higher risk of eczema in children at 9 months of age [31].…”
Section: Prenatal Birth Cohorts Investigating the Effect Of Vitamin Dmentioning
confidence: 90%